Reproductive Neuroendocrinology and Social Behavior - Tomoko Soga (Frontiers Research Topics, 2016)
Anti-social behaviors and social deficits induced mental disorders are critical problems in our society today. Social behaviors and interactions are shaped by experience, hereditary components (genes, hormones and neuropeptides) and environmental factors (photoperiods and metabolic signals). In addition to the classical gonadotropin-releasing hormone, RFamide peptides, kisspeptin and gonadotropin-inhibiting hormone are emerging as important regulators of the reproductive axis. These neuropeptides are evolutionarily conserved and are regulated by environmental factors. In this Research Topic, we advocate more recent advances in reproductive neuropeptides and sex steroids in the domains of social behavior including sexual and parental behavior, aggression, stress and anxiety. Using multiple species model, we also review how genes and the neuroendocrine system interact at the cell and organismic levels to contribute to social behavior in particular the epigenetic genomic changes caused by early life environment. We provide comprehensive insights of distinct neural networks and how cellular and molecular events in the brain regulate social behavior from a comparative perspective.